Prevalence and factors associated with water, sanitation and hygiene (WASH) facilities deprivation among children in Nigeria - Chima Victor; Joseph Ayodeji Kupoluyi; Funmilola Folasade Oyinlola; Victor Ojoajogwu Sule (BMC Pediatrics)
Abstract Background Water, sanitation, and hygiene (WASH) remain fundamental public health components for children's survival, growth, and development. In Nigeria, children under 18 years are most deprived of WASH, with about 70 per cent lacking access to facilities. There is paucity of information on factors associated with WASH facilities deprivation in Nigeria, especially in the context of children. Hence, this study examines the household and individual factors related to WASH facility deprivation among children 0–17 years old in Nigeria. Method A secondary analysis of the 2021 Nigeria Multiple Indicator Cluster Survey (MICS) was conducted to assess facility deprivations in WASH for children, along with associated determinants. A merged dataset comprising a total of 22,059 weighted observations from both the under-five children and children aged 5–17 years was used for this study. Frequency tables, pie charts and bar graphs were used to examine the prevalence of WASH facility deprivation among children. A Chi-square statistical test was performed to determine associated factors with child WASH facilities deprivation in Nigeria at a p-value of less than 0.05 level of significance. Results This study found that at least one-third of children in Nigeria were deprived of either one or more WASH facilities. Specifically, 32% were deprived of water, 40% were deprived of hygiene facilities and 67% were deprived of sanitation facilities. Children aged 5–9 (37.6%) were the most deprived of WASH facilities in Nigeria. Across all regions of the country, more children were deprived of sanitation when compared to water and hygiene. Overall, the wealth index and geopolitical zone significantly influenced access and availability of WASH facilities for children in Nigeria. Specifically, the education of the household head and wealth index are associated with access to sanitation facilities, place of residence is significantly associated with availability of water while access to hygiene facilities is significantly associated with the sex of the household head. Conclusion The study concludes that there is a correlation between factors and the increased likelihood of children experiencing WASH facilities deprivation. Although the influence of these factors increases based on determinants and varies by regional dimensions, there are still insufficient implementation practices where deprivation is minimal, and this is influenced by household and other factors.